Collodion Baby - A. A. Made Berastia Anis Savitri,; Ida Ayu Sri Kusuma Dewi (PT. Kalbe Farma Tbk., 2022)
Collodion baby (CB) is a rare dermatological condition worldwide of 1: 300.000 birth. A Collodion baby is a newborn whose entire body is covered with an adherent, supple, parchment-like membrane. Collodion baby in a manifestation of various hereditary conditions, including Harlequin orchestras’ (HI), lamelar orchestras’ (LI), non-bullous congenital ichtyosiform erythroderma (NBCIE), trichothiodystrophy metabolic disease, and endocrine disease. We report two collodion babies cases with peeling skin, passive movement, and poor feeding. Both cases were hospitalized in the humidity-controlled incubator. Water and topical treatment were used for daily bathing to prevent infection.